Current application of algae derivatives for bioplastic production: A review. (March 2022) - Dang, Bao-Trong; Bui, Xuan-Thanh; Tran, Duyen P.H.; Hao Ngo, Huu; Nghiem, Long D.; Hoang, Thi-Khanh-Dieu; Nguyen, Phuong-Thao; Nguyen, Hai H.; Vo, Thi-Kim-Quyen; Lin, Chitsan; Yi Andrew Lin, Kun; Varjani, Sunita
Graphical abstract: Highlights: Yields of starch and PHB can be increased through culture with nutrient starvation. Cyanobacteria are a suitable source of PHB during cultivation and harvesting. Inconsistency in the polysaccharide composition of seaweed affects yield extraction. Carrageenan is a good additive for the production of edible food packaging. Membrane photobioreactor could be a sustainable production of algal derivatives. Abstract: Improper use of conventional plastics poses challenges for sustainable energy and environmental protection. Algal derivatives have been considered as a potential renewable biomass source for bioplastic production. Algae derivatives include a multitude of valuable substances, especially starch from microalgae, short-chain length polyhydroxyalkanoates (PHAs) from cyanobacteria, polysaccharides from marine and freshwater macroalgae. The algae derivatives have the potential to be used as key ingredients for bioplastic production, such as starch and PHAs or only as an additive such as sulfated polysaccharides. The presence of distinctive functional groups in algae, such as carboxyl, hydroxyl, and sulfate, can be manipulated or tailored to provide desirable bioplastic quality, especially for food, pharmaceutical, and medical packaging. Standardizing strains, growing conditions, harvesting and extracting algae in an environmentally friendly manner would be a promising strategy for pollution control and bioplastic production.